2010
DOI: 10.1007/s12649-010-9017-7
|View full text |Cite
|
Sign up to set email alerts
|

Rice Husk Ash as a Supplementary Raw Material for the Production of Cellulose–Cement Composites with Improved Performance

Abstract: Rice husk is an agricultural by-product worldwide in large quantities available. This is a suitable biomass source for energy production. Compared to other agricultural by-products, the burned rice husk presents a high yield of ash (about 20%) mainly composed of silica that will be mostly amorphous when properly incinerated. Extensive research in the past three decades has allowed the introduction of rice husk ash (RHA) as a supplementary raw material in cement-based products, whereby significant improvements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 25 publications
1
7
0
1
Order By: Relevance
“…X-ray fluorescence analysis was used for determination of chemical composition. The silica content in the RHA was 73% that was in agreement with the previous published research and indicated high possible reactivity of RHA as pozzolanic/ cementing agent [16,17].…”
Section: Chemical Compostion Of Rhasupporting
confidence: 91%
“…X-ray fluorescence analysis was used for determination of chemical composition. The silica content in the RHA was 73% that was in agreement with the previous published research and indicated high possible reactivity of RHA as pozzolanic/ cementing agent [16,17].…”
Section: Chemical Compostion Of Rhasupporting
confidence: 91%
“…Sufficient grinding of RHA allows the dissolution of silica in the highly alkaline environment of the cement paste and the reaction of SiO 2 , Al 2 O 3 and Fe 2 O 3 existing in RHA with Ca(OH) 2 , produces C-S-H (calcium silicate hydrate), C-A-H (calcium aluminate hydrate) and C-A-F-H (calcium aluminate ferrite hydrate) that results in a higher densification of the matrix [38,39]. Also, the finest RHA particles tend to concentrate near the aggregate-matrix interface, leading to reduced porosity and enhanced internal bonding capacity [40].…”
Section: Introductionmentioning
confidence: 99%
“…A few of researchers proposed improved methods, for instance, Zhang et al [49] and Soda et al [50] found that rice husk ash had an obvious effect on co-composting with livestock manure and remediation of acidic polluted soil. Isoda et al [51] prepared activated carbon from rice husk, Conrado et al [52] introduced rice husk ash as a supplementary raw material in cement-based products. These study works provided a new approach for rice husk utilisation as a resource in China.…”
Section: Discussionmentioning
confidence: 99%